2022
DOI: 10.3390/ijerph191811576
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and Depressive Symptoms among Medical Staff in a Military Hospital Dedicated to the Treatment of COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) is prevalent around the world, and many studies suggest that depression among medical staff is on the rise during the pandemic. This study aims to assess the relationship between depressive symptoms and individual resilience among military hospital personnel responsible for treating patients with COVID-19. Individuals from the Armed Forces Daejeon Hospital who responded to the questionnaires from 8 February to 15 February 2022 participated in this study. Resilience and depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…However, when resilience is associated with other mental disorders, the presence of different degrees across multiple domains of life is questionable. Previous studies suggest that resilience is inversely related to mental disorders such as depression, anxiety, and somatization (Cal et al 2015;Roberts et al 2021;Lee et al 2022). Our study also found that a majority of individuals with depressive symptoms in both groups demonstrated significantly low resilience.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, when resilience is associated with other mental disorders, the presence of different degrees across multiple domains of life is questionable. Previous studies suggest that resilience is inversely related to mental disorders such as depression, anxiety, and somatization (Cal et al 2015;Roberts et al 2021;Lee et al 2022). Our study also found that a majority of individuals with depressive symptoms in both groups demonstrated significantly low resilience.…”
Section: Discussionsupporting
confidence: 78%
“…One was among nurses working in respiratory clinical areas, and their depressive symptoms and moderate or high resilience accounted for 17.2% and 65%, respectively (Roberts et al 2021). Another was among medical staff in a military hospital, and their depressive symptoms and high resilience accounted for 8.8% and 61.9% of the sample, respectively (Lee et al 2022). Nurses generally experience more depression, anxiety, and stress compared to other staff groups in hospitals (Mattila et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, heavy workloads and high occupational pressure have led to decreased job satisfaction, increased work burnout and even the emergence of presenteeism, which refers to situations in which workers appear to be on the job but are not actually working [ 6 ]. Especially during the COVID-19 pandemic, primary care workers came into close contact with suspected or confirmed patients; due to the resulting risk of infection as well as overwork, these workers thus faced physical and psychological pressure [ 7 ]. Such pressure affected the mental health of medical staff in both the short and long term.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have even identified depression, anxiety and post traumatic stress disorder symptoms as the result of the failure to utilize resilience to promote self-adjustment [ 14 ]. Several studies have shown that psychological resilience might protect individuals from severe stress and that this factor is negatively correlated with burnout and depressive symptoms among hospital personnel [ 7 , 15 , 16 ], thus suggesting that cultivating psychological resilience among primary care workers might be a promising way to protect medical staff from the negative psychological impacts of medical work and promote their mental health.…”
Section: Introductionmentioning
confidence: 99%